Clinical Considerations in the Approach to Vancomycin-Resistant Enterococci: A Narrative Review - John W. Beale; Marina Durward-Diioia (University Library System, University of Pittsburgh, 2022)
Vancomycin-Resistant Enterococci (VRE) increasingly colonize and infect assorted patient populations throughout the world, maintaining a continual reservoir of opportunistic pathogens with varying antibiotic resistance. Here we present the current general epidemiology and classification of these pathogens within the scope of healthcare-associated infections (HAIs). Risk factors for colonization and conditions for subsequent infection are reviewed, along with infection characteristics. Current infection control protocols and their effectiveness, selected evidence-based medical therapies, and ongoing research into alternative therapies are summarized.